A Methodology for Characterizing Gun Barrel Flexure due to Vehicle Motion. (2001) - Bundy, Mark; Newill, James; Marcopoli, Vince; Ng, Michael; Wells, Charles
Abstract : Barrel centerline curvature is known to influence the location of projectile shot impacts. Superimposed on the unique manufactured barrel centerline is the flexed barrel shape that can occur prior to firing while the vehicle is on the move. In order to understand and quantify the effects of barrel flexure on gun accuracy, it is necessary to determine what combination of fundamental mode shapes is most likely to occur. A method to accomplish this task is described in this paper. The method is demonstrated by enumerating the 10 most likely flexed barrel shapes that were found to occur in a tank-mounted gun barrel while it traversed a bump course.